2012
DOI: 10.1016/j.jhep.2011.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome RNA expression profiling of endoscopic biliary brushings provides data suitable for biomarker discovery in cholangiocarcinoma

Abstract: Background and aims Molecular analyses of biliary brushings using microarray and qPCR have the potential to provide valuable information on the biology of biliary diseases. Microarray analysis of biliary strictures has rarely been applied to endoscopic biliary brushings. Methods Biliary brushings were obtained from patients with benign and malignant biliary disease at the time of ERCP. Microarray analysis of mRNA isolated using brushings from ten patients was validated for a selection of genes by qPCR using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 20 publications
2
31
0
1
Order By: Relevance
“…The incidence thereafter was approximately 1% per year in those with dominant strictures. The high rate of CC (particularly at presentation) highlights the difficult clinical problem of differentiating malignant from benign dominant biliary strictures and demonstrates the need for improved diagnostic tests such as genomic studies and fluorescence in situ hybridisation (FISH) analysis which has been shown to improve the diagnostic accuracy of biliary cytology sampling [2122]. Those with new presentations of PSC with evidence of a dominant stricture require thorough evaluation in order to exclude the presence of super-imposed CC, with consideration of a full range of diagnostic tests at the time of ERCP, including exfoliative cytology, intraductal biopsy and cholangioscopy…”
Section: Discussionmentioning
confidence: 99%
“…The incidence thereafter was approximately 1% per year in those with dominant strictures. The high rate of CC (particularly at presentation) highlights the difficult clinical problem of differentiating malignant from benign dominant biliary strictures and demonstrates the need for improved diagnostic tests such as genomic studies and fluorescence in situ hybridisation (FISH) analysis which has been shown to improve the diagnostic accuracy of biliary cytology sampling [2122]. Those with new presentations of PSC with evidence of a dominant stricture require thorough evaluation in order to exclude the presence of super-imposed CC, with consideration of a full range of diagnostic tests at the time of ERCP, including exfoliative cytology, intraductal biopsy and cholangioscopy…”
Section: Discussionmentioning
confidence: 99%
“…Mouse Pvt1 is an oncogene that was originally identified as a common retroviral integration site in murine leukemia virus (MLV)‐induced T lymphomas . The human PVT1 oncogene, which is located at 8q24.21, was found to be up‐regulated in a series of human tumors . However, the precise mechanism of lncRNA‐hPVT1 and the downstream molecules associated with its action have not been described.…”
mentioning
confidence: 99%
“…Our analysis of the chip data from cholangiocarcinoma tissues (Chapman et al, 2012) identified several differentially expressed genes, including GSTA1 and GSTA3. According to the network analysis, these two genes interacted with CYP450 members and thus participate in the CYP450 exogenous chemical metabolism.…”
Section: Discussionmentioning
confidence: 97%
“…The data set GSE34166 (Chapman et al, 2012), including raw files and probe annotations, was downloaded from the Gene Expression Omnibus (GEO) database, which contains 10 biliary stricture samples, representing 4 benign and 6 malignant tissues (cholangiocarcinoma). Chip data were acquired by using the GPL570 [HG-U133_Plus_2] Affymetrix Human Genome U133 Plus 2.0 Array.…”
Section: Microarray Datamentioning
confidence: 99%